Validation of finite element analysis for a new external finger fixator to Correct flexion deformity – a preliminary result - Rahman, H.S.A.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Ahmad, T.S.; Ng, E.S. (Springer-Verlag Berlin Heidelberg 2008, 2008)
The purpose of this study is to validate of a new external finger fixator components by using finite element analysis (FEA). The new external finger fixator consists of proximal, middle and distal phalanges support sections and means for rigidly connecting each support to a hinge and its corresponding attached to phalanx through the movements of flexion or extension. The results from the analysis found that the entire components of the fixator conform to the performance based on the requirements for general duty (500 N load applied on uniformly distributed load). This analysis shows that the new external fixator is able to restore full function and dynamic range of motion for patients with flexion deformity at the finger joints without failure.